The Construction of Volatile Profiles of Eight Popular Peach Cultivars Produced in Shanghai Using GC-MS and GC-IMS - Xia Wang; Xiongwei Li; Mingshen Su; Minghao Zhang; Yang Hu; Jihong Du; Huijuan Zhou; Xianan Zhang; Zhengwen Ye; Xuelian Yang (Horticulturae, 2023)
Peach (Prunus persica L.) is an economically important fruit crop worldwide due to its pleasant flavor. Volatile organic compounds (VOCs) are vital factors for assessing fruit quality. Here, we constructed the VOC profiles for the top eight popular commercial peach cultivars produced in Shanghai by combining gas chromatography-mass spectrometry (GC-MS), odor activity value and gas chromatograph-ion mobility spectrometry (GC-IMS). Seventy VOCs were detected using GC-MS, of which twenty-three were commonly found in eight peach cultivars, including hexanal, nonanal, benzaldehyde, 2-hexenal, butyl acetate, hexyl acetate, (Z)-3-hexen-1-yl acetate, linalool, β-myrcene, D-limonene, 1-hexanol, 3-hexenol, 2-hexenol, 2-ethyl-1-hexanol, γ-octalactone, δ-decalactone, γ-hexalactone, γ-decalactone, γ-dodecalactone, β-ionone, 2-octanone, 2-ethyl furan and 2,4-ditert-butyl phenol. A total of 17 VOCs were screened on the basis of OAV ≥ 1 and the top 5 of this contribution were γ-decalactone, β-ionone, hexanal, 2-hexenal and linalool. Lactones had the highest OAV in HJML and terpenoids had the highest OAV in JC. JXIU had the lowest OAV of lactones and terpenoids. Based on the range of their OAV values, the flavor evaluation standard of Shanghai high-quality peach cultivars can be established, which is also a reference for breeding excellent offspring. Twenty-six VOCs were detected using GC-IMS, and the largest proportion were aldehydes. Principal component analysis (PCA) showed that Hikawa Hakuho (HH) and Jinchun (JC) were distant from the other samples, indicating that their volatiles were more distinct. These results provide a foundation for improving our understanding of aroma compositions in these high-quality peach cultivars, which might also provide a reference for future design breeding to improve fruit flavor.